A cumulative family risk index model: Delinquency and academic performance among Han Chinese and Native Taiwanese students. (July 2019) - Chen, Hsing-Jung
The present study was designed to add to extant knowledge on the cumulative family risk model from a culturally specific perspective in Taiwan. Using a nationally representative sample of adolescents ( N  = 16, 435), this study examined the relationships among cumulative family risk, delinquency, and academic performance. The results suggested that cumulative family risk was associated positively with delinquency and negatively with academic performance. The findings also revealed a moderating effect of ethnicity on academic performance but not on delinquency. The findings suggested that reducing cumulative family risk is important. Attention to ethnic groups' cultural values help in identifying mechanisms associated with youths' developmental outcomes.